2023
DOI: 10.1097/ftd.0000000000001055
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Drug–Drug Interactions Between Perampanel and Carbamazepine Using Enzyme Induction Model in Epileptic Patients

Abstract: Background: Perampanel (PER) is an oral antiepileptic drug and its concomitant use with carbamazepine (CBZ) leads to decreased PER concentrations. However, the magnitude of its influence may vary, depending on the dynamics of the enzyme induction properties of CBZ. This study aimed to develop a population pharmacokinetic (PPK) model considering the dynamics of enzyme induction and evaluate the effect of CBZ on PER pharmacokinetics. Methods: We retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…In line with the result from previous model analysis, 23 our study also found that a one‐compartment model with first‐order absorption and elimination could adequately characterize the pharmacokinetic profile of PER. After normalization to a median WT of 30.0 kg, the typical value of CL in our study was .020 L/h/kg, which is marginally higher than values reported in adolescent (.012–.014 L/h/kg) and adult populations (.010–.012 L/h/kg) 24–26 . This may be attributed to differences in the age range and ethnicity of the patients included, and sample size between the studies.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In line with the result from previous model analysis, 23 our study also found that a one‐compartment model with first‐order absorption and elimination could adequately characterize the pharmacokinetic profile of PER. After normalization to a median WT of 30.0 kg, the typical value of CL in our study was .020 L/h/kg, which is marginally higher than values reported in adolescent (.012–.014 L/h/kg) and adult populations (.010–.012 L/h/kg) 24–26 . This may be attributed to differences in the age range and ethnicity of the patients included, and sample size between the studies.…”
Section: Discussioncontrasting
confidence: 65%
“…After normalization to a median WT of 30.0 kg, the typical value of CL in our study was .020 L/h/kg, which is marginally higher than values reported in adolescent (.012-.014 L/h/kg) and adult populations (.010-.012 L/h/kg). [24][25][26] This may be attributed to differences in the age range and ethnicity of the patients included, and sample size between the studies. In this popPK analysis, WT, TBIL, and OXC were identified as influencing factors for the CL of PER.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous reports that the concomitant use of enzyme-inducing AEDs could result in lower PER concentrations or C/D, both in children and adults ( Patsalos et al, 2016 ; Gaudio et al, 2019 ; Ikemoto et al, 2019 ; Ishikawa et al, 2019 ). Carbamazepine could increase the clearance of PER in a population pharmacokinetic analysis ( Fujita et al, 2022 ). However, the influence of the enzyme inhibitor AED, valproic acid, was not identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that PER plasma levels were affected by otherAEDs in routine TDM practice, including carbamazepine, phenobarbital, valproate and topiramate ( Patsalos et al, 2016 ; Contin et al, 2018 ; Silva et al, 2023 ). A recent study indicated that enzyme-inductive AED could increase PER clearance ( Fujita et al, 2022 ). However, it is still unknown whether these drug interactions have impact on PER therapeutic target nonattainment.…”
Section: Introductionmentioning
confidence: 99%